Perancangan dan Implementasi Booking System Lapangan menggunakan Framework MVC berbasis Web - Haya Rasikhah; Ahmad Rio Adriansyah (LPPM STT Terpadu Nurul Fikri, 2022)
The community needs sports field rental to facilitate sports activities that require special equipment such as basketball hoops, net, goalpost, and others. The ordering system for sports fields is still less efficient in terms of time, effort, and cost because people have to go to the field to see field availability and place field orders. In addition to inconveniencing the field owner, the manual field ordering system also hinders the field owner in storing order data. Therefore, researchers built a website-based sports field ordering application that aims to simplify ordering sports fields. The method that researchers use in developing the application is the waterfall method. Researchers used questionnaires and interviews to collect data and tested the application using a Likert Scale and User Acceptance Testing (UAT). Functional test results show the application runs 100% with a feasibility level of 89.5% on the user system and 92.1% on the admin system, which means the application is feasible and can be used.